Mechanical and Microstructural Properties of A36 Marine Steel Subjected to Underwater Wet Welding - Eko Surojo; Raka Pungkas Aji; Triyono Triyono; Eko Prasetya Budiana; Aditya Rio Prabowo (Metals, 2021)
Underwater wet welding (UWW) is applied to repair basic offshore structures, underwater pipelines, water transportation, docks, and port equipment. The underwater wet welding method used in the current research was shield metal arc welding (SMAW), and this was conducted on an A36 steel plate. We investigated the effect of a water temperature of 10 ± 5 °C and different types of water flow (without flow, non-uniform flow with baffle bulkhead, and non-uniform flow without baffle bulkhead). The defects found on the specimen included spattering, irregular surfaces, porosity, and undercutting. A high cooling rate led to the formation of more acicular ferrite (AF) phases in the weld metal area than a slow cooling rate. The microstructure of the heat affected zone (HAZ) area led to the formation of finer and small grains. Values of tensile, impact, and hardness strength were greater with higher cooling rates. The highest tensile strength value was 585.09 MPa, and this occurred with non-uniform flow without a baffle bulkhead. The highest values of absorbed energy and impact strength were 41.9 J and 2.05 J/mm2, respectively, and these occurred with a non-uniform flow without a baffle bulkhead. The greatest hardness values were found with a non-uniform flow without a baffle bulkhead in the weld metal area.